KURIKULUM MERDEKA DAN PENGAJARAN BAHASA INGGRIS DI SEKOLAH DASAR: NEED ANSALISIS STUDY - Diana Oktavia; Nur Habibah; Levandra Balti; Ridho Kurniawan (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Merdeka Curriculum has been implemented since 2022 in all educational institutions, including in Elementary school. One of important things that highlighted in this new curriculum is teaching English in elementary school. This research aims to investigate the school needs related to Teaching English in Elementary School. This research involved 8 participants to provide the required data. It was conducted using qualitative method through interview and open-ended questionnaire. Based on the data, it was shown that the school is excited to implement this policy, but there are some school needs that have to be fulfilled, including the need of English teacher, the English language training for the elementary school teachers, and the facilities.